Myths of the north and origins of city-form: some reflections across history and prehistory - Akkerman, Abraham (Journal of Architecture and Urbanism, 2015)
Early environmental myths of the body and the sky have been instrumental in the emergence of prehistoric urban environments, and have continued to play an important role in urban design through history to this time. The notions of the body, as the absolutely immediate, and the sky, as the unreachably distant are shown here as precursors to the core proposition of mind-environment transactions, introduced by Walter Benjamin a century ago. Late prehistory and early antiquity manifest the idea of epochal and ongoing progression in mind-city interaction, specifically, as a gender-based configuration of edifice versus space, or volume versus void, in the built environment. The North Star, as a celestial feature representing permanency and solidity, was critical in the formation of masculine myths of the environment upon which the very notion of a designed edifice had been founded, and from which the early city had emerged. The feminine counterpart of the edifice is urban void, often the garden, the street or the city square. Whereas in Neolithic communities the open ritual space seems to have been the most important design element, city-form since antiquity has habitually accentuated the masculinity of edifices over designed voids. More feminine attituted drawing on prehistoric acumen can help refocusing the emphasis on urban volume, onto dynamic urban design of open public spaces for human movement in the city.